2019
DOI: 10.7150/ijbs.31099
|View full text |Cite
|
Sign up to set email alerts
|

miR-30e-5p Mitigates Hypoxia-Induced Apoptosis in Human Stem Cell-Derived Cardiomyocytes by Suppressing Bim

Abstract: Coronary microembolization can cause slow or no reflow, which is one of the crucial reasons for reverse of clinical advantage from cardiac reperfusion therapy. miRNAs and apoptosis are dramatically involved in the occurrence and process of cardiovascular diseases. Fortunately, human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have emerged as an appealing model for the evaluation of cardiovascular diseases. Therefore, our study was designed to explore the role of miR-30e-5p and apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Based on review of the literature (present study), miR‐30e‐5p modulates diverse mRNA targets in different disease situations, including cancer. These target genes are listed as follows: NFAT5 , TUSC3 , Bim , USP22 , MYBL2 , ITGA6 , ITGB1 , LRP6 and YAP1 . In our current study, miR‐30e‐5p was found to directly link to the 3′‐UTR domain of AEG‐1 mRNA, which accelerates the degradation of AEG‐1 mRNA and eventually reduces the level of AEG‐1 protein.…”
Section: Discussionsupporting
confidence: 49%
“…Based on review of the literature (present study), miR‐30e‐5p modulates diverse mRNA targets in different disease situations, including cancer. These target genes are listed as follows: NFAT5 , TUSC3 , Bim , USP22 , MYBL2 , ITGA6 , ITGB1 , LRP6 and YAP1 . In our current study, miR‐30e‐5p was found to directly link to the 3′‐UTR domain of AEG‐1 mRNA, which accelerates the degradation of AEG‐1 mRNA and eventually reduces the level of AEG‐1 protein.…”
Section: Discussionsupporting
confidence: 49%
“…Indeed, several studies describe little or no response to I/R-mimetic conditions in unprimed hPSC-CMs, although showing minimal but relatively significant cardioprotection by the individual molecules of interest (Hsieh et al, 2015;Wei et al, 2017;Mo et al, 2019). Our own experiments with oxygen/glucose deprivation in microfluidic devices show clearly divergent responses of postnatal murine cardiomyocytes and unprimed hPSC-CMs characterized by abnormal intracellular glycogen stores (Martewicz et al, 2018).…”
Section: Ischemia/reperfusion Injury Modelingmentioning
confidence: 71%
“…For example, miR-30e in the myocardium is inhibited after the occurrence of coronary microembolization, together with decreased cardiac function 27 . miR-30e alleviates apoptosis induced by hypoxia in human stem cell-derived cardiomyocytes 28 . Of note, the effect of miR-30e on cardiomyocyte hypertrophy was reported in a series of cellular and animal studies.…”
Section: Discussionmentioning
confidence: 99%